Main Debates on the Management of Mental Illness: 1990-2020. A narrative review - Grech, Paulann; Grech, Reuben (European Journal of Mental Health, 2022)
Introduction: Since the introduction of newer psychiatric treatment methods during the 20th century, debates about the effectiveness andappropriateness of such treatment have featured. Advocates among those who promote the sociological, biological, psychological and spiritual understandings of mental illness and its treatment have created tangible tensions with those supporting each position commonly indulging in fierce attacks on the others. Aims: The aim of this paper is to explore some of the principal treatment viewpoints that characterized the late 20th century (1990 onwards) and early 21st century (up till 2020). Ultimately, these debates guided contemporary practice towards a biopsychosocial-spiritual view of mental illness in a move towards holistic person-centered care, which nowadays is the advocated model in many health systems. Methods: The authors undertook a literature search in order to locate published debates on psychiatric treatment during the late 20th century (1990 onwards) and the early 21st century (up till 2020). Results: Debates emerging from 36 articles were identified and synthesized in a narrative review. Conclusions: Exploring the various debates that have characterized mental health care serves as a crucial reflective exercise on what needs to be considered when claiming that contemporary care is based on a holistic and person-centered approach. In this view, critical evaluation is needed so as to avoid repeating the coercive and inhumane mistakes of the past.